Thermal degradation kinetics of polyesters containing mesogenic aromatic diols - Mule, Smita Atmaram; Ghadage, R. S.; Jacob, Nalini E.; Rajan, C. R.; Ponrathnam, Surendra (Journal Applied Polymer Science, 2005)
A series of polyesters were synthesized by reacting structurally differing aromatic diols with either saturated (flexible) or unsaturated (rigid) dicarboxylic acid halide by a stirred interfacial polycondensation technique. Thermal degradation kinetics of these polyesters were investigated by applying Coats-Redfern and Horowitz-Metzger nonisothermal procedures. The dynamic thermogravimetry experiments were conducted in nitrogen to obtain differential thermogravimetric plots. Thermal stability of these polyesters was discussed on the basis of semiquantitative methods such as differential procedural decomposition temperature, integral procedural decomposition temperature, and fraction decomposition temperature (e.g., 10 % DT). Degradation proceeded in multiple stages. The thermal degradation patterns and activation energies in these stages were discussed in relation to central bridging moieties of aromatic diol. The activation energies of these polyesters were found to be in the range of 100 to 200 kJ/mol. The effect of spacer type on activation energy was also reported. (c) 2005 Wiley Periodicals, Inc.
Keywords: Activation energy; Degradation; kinetics (polym.); Polycondensation; polyesters

Transfer of technology (ToT) document of polyimide binder resins - Ponrathnam, Surendra; Chelanattukizhakkemadath, Raman Rajan; Dwivedi, Mayank; Chavan. N. N.; Qureshi, Moham; Bhongale, Sunil Sitaram; Rao, Locanindi Hari Sarvothama; Dhansekharan, Janakiraman; Mohan, S. Krishna; Deokar, Sarika Babasaheb; Momin, Mohasin Shamshuddin (2009)

Transfer of technology (ToT) document of ethyl silicate-32 - Ponrathnam, Surendra; Chelanattukizhakkemadath, Raman Rajan; Dwivedi, Mayank; Chavan, Nayaku; Qureshi, Moham; Bhongale, Sunil Sitaram; Rao, Locanindi Hari Sarvothama; Dhanasekharan, Janakiraman; Mohan, S. Krishna; Deokar, Sarika Babasaheb; Momin, Mohasin Shamshuddin (Transfer of Technology (ToT)/ Technical Documents, 2011)

Transfer of technology (ToT) document of phenol-aniline-formaldehyde (sf-342a) resins - Ponrathnam, Surendra; Chelanattukizhakkemadath, Raman Rajan; Dwivedi, Mayank; Chavan, Nayaku; Qureshi, Moham; Bhongale, Sunil Sitaram; Rao, Locanindi Hari Sarvothama; Dhanasekharan, Janakiraman; Mohan, S. Krishna; Deokar, Sarika Babasaheb; Momin, Mohasin Shamshuddin (Transfer of technology (ToT) document, 2011)